PENGARUH PENGGUNAAN GADGET TERHADAP ORIENTASI BUDAYA POLITIK SISWA DI KABUPATEN LAMPUNG TIMUR - Fitra Endi Fernanda; Tahta Herdian Andika (Jurnal Agregasi, 2022)
This study aims to determine the effect of utilization of gadget as political communication towards the political culture orientation of students in senior high school. The design in this study is descriptive research using a quantitative approach and using correlational research. The sample in this study was taken from the population with a proportional purposive sampling technique that was as many as 347 students. The results in this study indicate that there is a positive and significant influence between the utilization of gadget as political communication towards. This is indicated by the t-count values is 6,398> t-table (6,398 > 1,649) and a significance value <0,05 (0,000 < 0,05)